2011
DOI: 10.1007/s00418-011-0815-1
|View full text |Cite
|
Sign up to set email alerts
|

Role of apolipoprotein E in renal damage protection

Abstract: It is well-known that nephrotic syndrome and chronic renal failure are associated with lipid and lipoprotein abnormalities. For a long time, it has been thought that hyperlipidemia is a secondary and insignificant condition of these renal injuries. Recently, it has been shown that dyslipidaemia may contribute to the development and progression of chronic kidney disease. Apolipoprotein E (apoE) null mice are a very popular model for studying spontaneous hypercholesterolemia, but only limited data are available … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…2002; Bonomini et al. 2011), and laboratory mutants show a number of physiological and morphological changes similar to kidney disease phenotypes (Bonomini et al. 2011).…”
Section: Resultsmentioning
confidence: 99%
“…2002; Bonomini et al. 2011), and laboratory mutants show a number of physiological and morphological changes similar to kidney disease phenotypes (Bonomini et al. 2011).…”
Section: Resultsmentioning
confidence: 99%
“…It was also shown that mitochondrial ROS enhanced telomere-dependent senescence (Passos et al, 2007 ). Likewise, some authors showed the link between telomere length and metabolic disease suggesting increased cellular turnover and therefore accelerated cell aging (Bonomini et al, 2011 ; Kong et al, 2013 ). The increasing abdominal adiposity typical of the MetS is accompanied by accelerated telomere attrition (Révész et al, 2015 ).…”
Section: Pathophysiologymentioning
confidence: 98%
“…According with this theory a study by Passos et al 2007 demonstrated that the senescent cells had higher ROS levels, dysfunctional mitochondria, more DNA double-strand breaks and shorter telomeres and it was shown that mitochondrial ROS enhanced telomeredependent senescence [137]. Recently, some authors showed the link between telomere length and metabolic disease suggesting increased cellular turnover and therefore accelerated cell aging [138,139]. …”
Section: Aging and Methabolic Syndromementioning
confidence: 99%